Audit Quality and Financial Statement Manipulation: The Moderating Effect of Tone at the Top - Marais, Alastair (International Journal of Economics and Financial Issues, 2024)
South Africa has recently fallen victim to numerous major corporate frauds. This has called into question South Africa’s audit quality, as indicated by its loss of the number one place for auditing and reporting standard strength, according to the World Economic Forum. This study examined the moderating effect of tone at the top on the relationship between audit quality and financial statement manipulation. Using a South African sample of 829 firm-year observations from 2011 until 2018, principal component analysis was used to construct two audit quality variables (competence and independence) and two tone at the top variables (autocratic and pragmatic). Financial statement manipulation was measured using fraud and discretionary accruals. The findings revealed that while an autocratic tone strengthened the negative relationship between audit quality and fraud, it also resulted in higher income-increasing discretionary accruals. This study contributes to the audit quality literature in South Africa by revealing how the tone at the top can affect the auditor’s ability to conduct a quality audit. The results will interest auditors and shareholders seeking to reduce fraud and earnings management.